Deposit flight and capital controls: a tale from Greece - Rousakis, M; Priftis, R (University of Oxford, 2017)
This paper presents an analytical narration of the later stages of the Greek crisis, focusing on two key events that unfolded during 2014-2015 and set Greece apart from other episodes of sovereign debt crises: the risk of Grexit and the imposition of capital controls on the banking sector. To account for them both, we extend the standard small open economy environment along three dimensions. First, we allow for an informal sector. Second, we allow for a richer menu of assets that include cash, which is needed for informal consumption and is costly to hold. Third, we introduce a banking sector that turns households' deposits into capital. We show that a risk of Grexit leads households to run down their deposits to the detriment of bank balance sheets, increase their demand for cash, and increase their consumption whilst reallocating it towards formal goods. As evidenced by the data capital controls mitigate the deposit ight and reinforce the switch of consumption to formality.